+0

# e calculation

0
56
1

e^w+22=21e^-w

Guest Oct 15, 2017
Sort:

#1
0

Solve for w over the real numbers:
e^w + 22 = 21/e^w

21/e^w = 21 e^(-w):
e^w + 22 = 21/e^w

Multiply both sides by e^w:
22 e^w + e^(2 w) = 21

Simplify and substitute x = e^w.
22 e^w + e^(2 w) = 22 e^w + (e^w)^2
= x^2 + 22 x:
x^2 + 22 x = 21

x^2 + 22 x + 121 = 142

Write the left hand side as a square:
(x + 11)^2 = 142

Take the square root of both sides:
x + 11 = sqrt(142) or x + 11 = -sqrt(142)

Subtract 11 from both sides:
x = sqrt(142) - 11 or x + 11 = -sqrt(142)

Substitute back for x = e^w:
e^w = sqrt(142) - 11 or x + 11 = -sqrt(142)

Take the natural logarithm of both sides:
w = log(sqrt(142) - 11) or x + 11 = -sqrt(142)

Subtract 11 from both sides:
w = log(sqrt(142) - 11) or x = -11 - sqrt(142)

Substitute back for x = e^w:
w = log(sqrt(142) - 11) or e^w = -11 - sqrt(142)

e^w = -11 - sqrt(142) has no solution since for all z element R, e^z>0 and -11 - sqrt(142)<0:
w = log(sqrt(142) - 11)    Log here is "natural log(ln)"

Guest Oct 15, 2017
edited by Guest  Oct 15, 2017

### 9 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details